Independensi Intelectual Capital pada Value creation asset dan modal - Yuni Utami; Adilah Permananingrum; Ira Maya Hapsari (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the Value Added of Intellectual Capital (Capital Coefficient (CC), Human Capital (HC), Structural Capital (SC) to see the impact on profitability on assets and equity in the Indonesian capital market. The sample taken is stocks that enter in the LQ45 index sector for the 2018–2020 period. The research is quantitative with a descriptive approach, purposive sampling technique and the Eviews 10 analysis tool. The results of the study prove that the Value Added Capital Coefficient (CC) has an effect on Value Creation Assets, while Human Capital (HC) and Structural Capital (SC) has no effect, while from a profitability perspective, the value added capital coefficient (CC) also affects Value Creation Equity, while Human Capital (HC), Structural Capital (SC) does not. effect on Value Creation Equity. These results prove that for companies, which has a high market capitalization and trading volume is influenced by the Value Added Capital Coefficient (CC), while in terms of Human Capital (HC), Structural Capital (SC) has no effect when viewed from the company's Intellectual Capital. The research contribution is that the value added from intellectual capital will lead to value creation both in terms of assets through Return on assets and capital through Return on Equity which is an important element for the company's financial sustainability.